Relationship between Pre Treatment Bacillary Load and Smear Conversion and Treatment Outcome of Pulmonary Tuberculo-sis Patients in a TB Unit of Karnataka - Anandaraj, R; Kavithai P, Pamagal; Anurupa , MS; Karthik, C` (National Journal of Community Medicine, 2017)
Background: Sputum smear microscopy is the key diagnostic tool used for case detection in RNTCP. Objectives: Among sputum smear positive pulmonary tuberculosis patients, 1. to study the relation between pre-treatment bacillary load and sputum smear conversion & 2. to study the relation between pre-treatment bacillary load and treatment outcome. Methodology: A prospective cohort study was conducted in Davangere TB unit, Karnataka. All sputum smear positive pulmonary tuberculosis patients registering under RNTCP in 2014 were interviewed using a structured questionnaire. Results: About 95.5% of the study subjects in Low Positive (LP) category finally achieved smear conversion, while only 87.4% of those in High Positive (HP) category could achieve the same (p=0.01). Favorable outcomes at the end of treatment were achieved by 73.6% of subjects in LP category as compared to only 60.7% of the HP category (p=0.01). Conclusion: A higher initial sputum smear grading of 3+ was associated with lower conversion and cure rates.